Respuesta :
[tex]f(x + 1) = (5/2)*f(x)
f(x + 1) = 2.5*f(x), f(1) = 3.2
f(2) = 2.5f(1) = 2.5*3.2 = 8
f(3) = 2.5f(2) = 2.5*8 = 20
f(4) = 2.5f(3) = 2.5*20 = 50
f(5) = 2.5f(4) = 2.5*50 = 125[/tex]
Answer:
[tex]f(5)=125[/tex]
Step-by-step explanation:
The complete question is
What is f(5) if f(1) = 3.2 and f(x + 1) =5/2 (f(x))?
By given,
[tex]f(1)=3.2[/tex] and [tex]f(x+1)=\frac{5}{2}(f(x))[/tex]
Now, we need to replace one be one until we get [tex]f(5)[/tex], because the given function is a sequence, so
For [tex]x=1[/tex]
[tex]f(x+1)=\frac{5}{2}(f(x))[/tex]
[tex]f(1+1)=\frac{5}{2}(f(1))\\f(2)=2.5(3.2)=8[/tex]
Then, for [tex]x=2[/tex]
[tex]f(2+1)=\frac{5}{2}(f(2))\\f(3)=2.5(8)=20[/tex]
We repeat the process until we get [tex]f(5)[/tex],
For [tex]x=3[/tex]
[tex]f(3+1)=\frac{5}{2}(f(3))\\f(4)=2.5(20)=50[/tex]
For [tex]x=4[/tex]
[tex]f(4+1)=\frac{5}{2}(f(4))\\f(5)=2.5(50)=125[/tex]
Therefore, if [tex]f(1)=3.2[/tex] and [tex]f(x+1)=\frac{5}{2}(f(x))[/tex], then [tex]f(5)=2.5(50)=125[/tex]